Sistem Informasi Akademik Mobile Berbasis QR Code dan Geolocation untuk Monitoring Kehadiran Siswa - Nissan Abdul Agung; Rr. Hajar Puji Sejati (TIN: Terapan Informatika Nusantara, 2026)
Digital transformation in the education sector encourages schools to adopt information systems that improve the efficiency and accuracy of academic data management. This study aims to develop and evaluate a mobile-based academic information system integrated with student attendance validation at SMAN 1 Sliyeg. The main problem identified is the inefficiency of manual attendance recording, which leads to delays in reporting and a high risk of data errors. The system is developed using a client-server architecture that integrates web and mobile platforms. The mobile application is built using Flutter, while the backend uses PHP and MySQL. Attendance validation is implemented through QR Code scanning combined with geolocation to ensure accurate user location verification. The system testing method used in this study is black-box testing to evaluate system functionality and User Acceptance Testing (UAT) to measure user acceptance of the developed system. The test results show that all system features function properly with a success rate of ≥ 90% in functional testing scenarios. In addition, the UAT results indicate that user satisfaction is categorized as good to very good. The results show that the developed system improves the effectiveness of academic data management, reduces recording errors, and accelerates the reporting process. Furthermore, the system enhances transparency and increases parents’ involvement in monitoring students’ academic progress. The main contribution of this study is the development of a mobile-based academic information system that integrates QR Code and geolocation technologies with ±100 meter radius for attendance validation, providing a more accurate, secure, and tamper-resistant attendance mechanism. Furthermore, this study offers a practical model for implementing digital transformation in secondary schools, which can serve as a reference for other educational institutions seeking to develop integrated and mobile-based academic information systems.